Automating with STEP 7 in STL and SCL : - Berger, Hans (Publicis Corporate Pub., 2007)
Statement list (STL) and structured control language (SCL) are the text-oriented programming languages in the programming software STEP 7. Now in its fourth edition, this book is an introduction into the latest version of STEP 7. It describes elements and applications for use with both SIMATIC S7-300 and SIMATIC S7-400, including the applications with PROFINET. It is aimed at all users of SIMATIC S7 controllers. First-time users are introduced to the field of programmable controllers, while advanced users learn about specific applications of the SIMATIC S7 automation system. SIMATIC is the worldwide established automation system for implementing industrial control systems for machines, manufacturing plants and industrial processes. Relevant open-loop and closed-loop control tasks are formulated in various programming languages with the programming software STEP 7